Spanglish [videorecording (DVD)] - Sandler, Adam; Leoni, Téa, 1966-; Vega, Paz, 1976-; Leachman, Cloris; Bruce, Shelbie, 1992-; Steele, Sarah, 1988-; Hyland, Ian, 1995-; Luna, Victoria (Columbia TriStar Home Entertainment, 2005)
When Flor and her daughter, Cristina come to the United States, Flor gets a job as a maid at the home of a successful chef, John Clasky, his insecure wife, Deborah, their two children, and Deborah's mother. Despite Flor's lack of English, she does the best she can to assist the Clasky family in more than just house cleaning matters. However, when Flor is forced to live with the family over the summer, she has no choice but to bring Cristina along. Deborah, much to Flor's disliking, treats Cristina much like her own and at the same time she hurts the feelings of her own daughter, Bernice. When John's dreams begin to unravel, he begins to feel like his whole world is coming down around him. Told through Cristina's college letter to Princeton University, Cristina learns that things come and go in life, but family is the most important thing a person can have.